1993
DOI: 10.1002/1097-4679(199307)49:4<563::aid-jclp2270490414>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

The effects of written autobiographical recollection induction procedures on mood

Abstract: This study assessed the effects of group induction procedures that are practical in their administration (written format) and also individualized. Fifty‐ four females and 36 males were assigned randomly to one of three conditions. Conditions One and Two consisted of subjects being asked to think of the two saddest or two happiest events of their lives, respectively. Condition Three consisted of a control condition in which subjects were asked to read a geography article. The procedure produced marked decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 6 publications
(1 reference statement)
2
31
0
Order By: Relevance
“…Other MIPs considered include written procedures (Baker & Gutterfreund, 1993), listening to music (Pignatiello et al, 1986;Västfjäll, 2001), and watching film clips 8 (Hewig et al, 2005). The imagery task was eventually selected after a review of several meta-analyses of MIP effectiveness and validity (see Gerrards-Hesse, Spies, & Hesse, 1994;Larsen & Sinnett, 1991;Westermann, Spies, Stahl, & Hesse, 1996), which suggested that the imagery task would most efficiently induce stable and reasonably intense moods for the purpose of this study.…”
Section: Mood Inductionsupporting
confidence: 52%
“…Other MIPs considered include written procedures (Baker & Gutterfreund, 1993), listening to music (Pignatiello et al, 1986;Västfjäll, 2001), and watching film clips 8 (Hewig et al, 2005). The imagery task was eventually selected after a review of several meta-analyses of MIP effectiveness and validity (see Gerrards-Hesse, Spies, & Hesse, 1994;Larsen & Sinnett, 1991;Westermann, Spies, Stahl, & Hesse, 1996), which suggested that the imagery task would most efficiently induce stable and reasonably intense moods for the purpose of this study.…”
Section: Mood Inductionsupporting
confidence: 52%
“…In this task, participants were asked to recall and write about a time when they either felt intensely rejected, a time when they experienced an intense academic failure, or their walk or drive to campus that day. Similar to mood inductions that rely on autobiographical recall to instantiate particular moods (e.g., Baker & Guttfreund, 1993), we expected that this recall exercise would lead participants to relive the original events and would place participants in the same state of mind they were in during the time of the original event. The failure recall condition was included as a negative control that was predicted to elicit similar levels of negative affect as the rejection condition while not manipulating feelings of social exclusion.…”
Section: Reliving Taskmentioning
confidence: 99%
“…Among the simple MIPs, autobiographical recall is one of the most commonly used methods in research. It is considered one of the most effective MIPs (Baker & Gutterfreund, 1993) and as the best technique for inducing positive mood (Strack, Schwarz, & Gschneidinger, 1985). This technique has been successfully used in several studies to induce (positive and negative) mood states in participants tested individually or in small groups (e.g., Bless et al, 1996;Bodenhausen, Kramer, & Süsser, 1994;Brewer, Doughtie, & Lubin, 1980;Jallais & Corson, 2008;Krauth-Gruber & Ric, 2000).…”
Section: P Smentioning
confidence: 99%